Writing Instruction under the Competency-Based Approach in Algerian Secondary Schools Traditions Realities and Perspectives - ADJEROUD, Safia; BELOUAHEM, Riad (Journal of Human Sciences, 2020)
The present study aims at investigating the teachers’ views on the teaching of writing within the scope of the Competency-Based Approach (CBA) at second year secondary school level, and more importantly at bringing into view the teaching realities and classroom practices, with the intent to negotiate and hopefully scheme the quest for rendering writing instruction more effective. Assuming that effective writing instruction under the CBA partly results from teachers’ awareness and consideration of the principles of the subject approach in the process of teaching writing, a questionnaire has been designed and administered to eighty-three secondary school teachers of English in Jijel. The results denoted the existence of some incongruity between the teachers’ views and their classroom practices, making the teaching of writing a rule of thumb activity.